Los pulgones (Homoptera: Aphidae) y sus enemigos naturales en la naranja, Citrus sinensis (L.), en la zona centro de Tamaulipas, México - Gaona García, Griselda; Ruíz Cancino, Enrique; Peña Martínez, Rebeca (Instituto de Ecología, A.C., 2000)
Aphid samplings were accomplished at three Valencia orange orchards in the municipalities of Hidalgo, Padilla and Victoria, Tamaulipas, from September 1995 to April 1996 during 12 collecting dates. Fifteen trees per orchard were sampled and infested shoots were collected from three strata of the tree height. The aphid species found were Aphis gossypii (Glover), Aphis spiraecola (Patch), Aphis fabae (Scopoli) and Toxoptera aurantii (Boyer de Fonscolombe) in a contagious distribution; medium stratum was the most preferred. The absence of Toxoptera citricida (Kirkaldy) during the period of study was confirmed. Natural enemies found were four Coccinellidae species (Hippodamia sp., Cycloneda sp., Brachyacantha sp. and Stethorus sp.), two Syrphidae species (Ocyptamies sp. and Pseudodorus clavatus Fabricius), one Chrysopidae (Chrysoperla rufilabris Burmeister) and one Chamaemyiidae (Leucopis sp.) as predators; Lysiphlebus testaceipes (Cresson) (Braconidae) as primary parasitoid, and Alloxysta megouzae (Ashm.) (Cynipidae) as a secondary parasitoid.